The Impact of COVID-19 Pandemic to UNAI - Limbong, Albinur (8ISC Abstract Proceedings, 2022)
Covid-19 pandemic has hit Indonesia or even the world since early 2020 Indonesia, many people have suffered from the disease due to the pandemic, and even some of them have died. Besides killing so many people, the Covid-19 pandemic has been a nightmare for many people living in this world. It has been destroying our economics, or even every aspect of our life, including education. The Indonesian government has applied a lockdown regulation, where people must work from home. No exception, UNAI has to change from offline teaching to become online teaching, although UNAI is a dormitory school. Due to the sudden change in teaching and learning processes, there should be an impact on student achievement, faculty performance, or even UNAI as an institution. It is interesting to ask whether the covid-19 pandemic brings negative effects or are there any positive effects. The purpose of this study is to see whether the Covid-19 pandemic influences student, teachers, or even UNAI’s performance. The performance of students is seen by the GPA (Grade Point Average), while the teacher performance is seen by teacher evaluation and the performance in research and publications. The parameters of UNAI performance involve students' and teachers’ performance, besides other institutional indicators, such as financial, ranking and accreditation, etc. The study was carried out from March 2020 until June 2021. The results of the study show that the covid-19 pandemic brought a positive impact on the academic achievement of UNAI students since there was a significant increase in GPA from 3.21 to 3.27. However, in terms of student evaluation on teacher performance, there was a slight decrease of 4.413 to 4.386; the decrease was not significant. The percentage of teachers published in a recognized journal and book publication increased from around 40% to 50%. Institutionally, UNAI performed even better during the pandemic in terms of the webometrics world ranking, accreditation, and financial indicators (working capital, liquidity, and cash). In conclusion, regardless of its negative sides, the covid-19 pandemic has brought a positive impact on UNAI. Covid-19 pandemic is like a blessing in disguise to UNAI. Keywords : university, students, covid-19, impact